The business capacity of broiler farmers in the partnership business pattern - Suryanti, R.; Sumardjo, S.; Syahyuti, S.; Tjitropranoto, P. (Diponegoro University, 2019)
The present study was conducted to analyze the broiler farmers’ capacity level in the partnership pattern and to analyze the factors which affect it. The current study was conducted in Bogor and Sukabumi, West Java Province using a survey approach on 247 farmers who ran farm businesses with the partnership pattern. Data were collected through questionnaire filling by farmers and in-depth interviews with key informants. The data were collected from July to October 2018. The data were analyzed descriptively and with inferential analysis (regression). The results of the study revealed that the farmers’ business capacity was weak. This was evident in the managerial and partnership capability which was categorized as low, the entrepreneurship and problem-solving capability which was categorized as medium, and only the technical capability which was categorized as high. The regression results demonstrated that business capacity was influenced positively by the formal education level, social environment characteristics (organizational support, access to experts), and the role of private extension agents (their role as educators, communicators, consultants, dynamizators, and organizers).